From Rote Learning to Creative Learning: An Action Research on AI Assisted Project-Based Pedagogy in a CBSE School - Dr. Alka Kapur, (Journal of Computational Analysis and Applications (JoCAAA), 2024)
The purpose of present study is to investigate the effectiveness of the AI-empowered projectbased pedagogy to shift from the traditional rote learning to the creative and competencybased learning among the secondary school students in CBSE School. This study was done over a period of 10 weeks intervention with the total sample of 90 students from class VIII,IX and X using an action research approach with mixed-methods